A DYNAMICALLY DEVELOPING HUNGARIAN SPA TOWN: MÓRAHALOM - Zita MARTYIN (European Journal of Geography)
The paper presents the case of a small town located in Southern Hungary: Mórahalom. Although a hundred years ago Mórahalom has not even been incorporated as a separate town, today it is one of the most successful municipalities in the region. For the last few decades, agriculture has been the dominant economic sector in the region, but then massive investments have been made to the spa industry, contributing to the development of Mórahalom. The aim of this paper is to present how the changes (especially in the tourism sector) have affected the development of the town and the lives of the residents of Mórahalom. The paper is based on secondary – analysis of local media and statistical data – and primary data (interviews). Results show that well founded planning and the appropriate utilisation of local conditions may enable the transformation of a lesser-known town into a significant tourist destination. The data prove that tourism contributed to the renewal and economic prosperity of the town. The case of Mórahalom may be instructive for other municipalities to see that achieving only a certain degree of success is not enough to sustain competitiveness in the tourism market; a continuous extension of offers and constant improvement are also necessary.